Analysis of Maqashid Sharia Perspectives in the Concept of Social Safety Net (Social Safety Net) - Naiza Assyafa Amisa Rizki; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
Amidst the dynamics of social change and rapidly evolving global challenges, economic uncertainty, inequality and poverty are the main highlights. This research aims to identify the principles of Maqashid Sharia in JPS and analyze the implementation of Islamic ethical values in these programs. The research results show the success of the JPS program in integrating Maqashid Sharia principles holistically, including the protection of life, property, religion, reason and descendants. The JPS program not only provides financial assistance, but also empowers through skills development and training to help individuals or groups get out of vulnerable conditions independently. With a qualitative literature review approach, this research produces an in-depth understanding of the contribution of Islamic ethical values in increasing the effectiveness and fairness of JPS programs. This research provides valuable guidance for the development of policies that are more grounded in Islamic moral and spiritual principles, so that JPS programs can continue to develop and provide maximum benefits for communities in need.